Prevalence and risk factors of polycystic ovary syndrome among reproductive-aged women - Khatun, Hasina; Rahman, Reefaat; Halim, Tanzila; Khan, Amena; Hasan, M. Mehedi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: PCOS is one of the most common reproductive and hormonal health issues that Bangladeshi women and young girls’ experience, yet many remain unaware of their condition until later in life. This study assessed the prevalence of and examined the factors of polycystic ovary syndrome (PCOS) among reproductive-aged women. Methods: This study cross-sectional included 500 patients diagnosed with PCOS who visited the department of obstetrics and gynecology, BSMMU, Dhaka, Bangladesh. This 2-years-long study included reproductive-aged women who were suffering from PCOS. Data were collected using a structured questionnaire that was administered to participants. The prevalence percentage of physician-diagnosed PCOS was calculated. A multivariable logistic regression model was employed to determine the adjusted odds ratios (aOR) and the corresponding 95% confidence intervals (CI) for the factors significantly associated with PCOS status. Results: Out of the 500 participants, the majority were single (85%), and the age group of 21 to 25 years comprised 56% of the participants. The prevalence of polycystic ovary syndrome (PCOS) was found to be 61% out of 500 participants affected. The risk factors that were significantly associated with PCOS included. Menstrual irregularities [adjusted odds ratio (aOR) =7.67; 95% confidence interval (CI): 3.72-15.83], family history of PCOS (aOR =5.11; 95% CI: 2.32-11.31), Hirsutism (aOR=3.55; 95% CI: 2.06-6.21) and Male pattern baldness (aOR=2.06; 95% CI: 1.19-3.58). Conclusions: This study revealed a moderately high prevalence of PCOS. Menstrual irregularities, obesity, a family history of PCOS, hirsutism, and baldness were significantly associated with the status of PCOS in the study sample.